Perancangan Aplikasi Monitoring Penerimaan dan Pelaksanaan Proyek Berbasis Web dengan Metode Prototyping Pada PT. Fas Jawara - Agus Waluyo; Aang Munawar (ISB Atma Luhur, 2017)
The rapid development of today’s tehnology makes itu possible to tranform a manual system to a computerized system. And it can also be applied to PT.Fas jawara who is still using manual system in recording the receipt of the project, work order making, news making events and invoices. Monitoring the implementation of information systems PT.Fas Jawara can provide benefits that such work would be more effective and efficient. Methodolody of data collection and analysis using theoretical analyzes and acceptance of information systems in general and monitoring projects are running. And inteviews with the company concerned to find out the problems and to investigate the acceptance of business process projects, making work order, create invoices and news system that runs the show. For the analysis and design of information system is using with the object oriented approach where evertything is described in the notation. At least the acceptance of information system and monitoring can runs as excected and allows users to apply